Анализ процессов в индукторной системе с притягивающим экраном, возбуждаемой внешним круговым соленоидом - Чаплыгин, Евгений Александрович (НТУ "ХПИ", 2015)
В статье представлен теоретический анализ пространственно-временных распределений индуцированных токов и сил притяжения в «индукторной системе с притягивающим экраном», возбуждаемой плоским круговым соленоидом, расположенным с внешней стороны вспомогательного экрана. Показана, достаточно высокая эффективность системы, что позволяет рекомендовать её как инструмент внешней рихтовки вмятин в кузовных покрытиях автотранспорта.

Introduction. Developments in the field of magnetic-pulse treatment of metals (MPTM) are increasingly used in the modern technologies of production and repair of the aviation, automotive and other machinery, as they are environmentally friendly and energy-efficient incomparison with classical approaches. One of the main components of the device MPTM is a tool – inductor or the inductor system with an attractive screen (ISAS). The calculated dependences to calculate the inductor system with an attractive screen were taken from previous works. The ratios were obtained for the low-frequency mode of the excited fields, when is place their significant penetration through a thin-walled metal screen and a deformed workpiece. As it was shown earlier this mode is the most efficient from point of view of a force action on the object of a processing. Purpose. The theoretical analysis of the spatial-temporal distributions of the induced currents and forces of an attraction in the inductor system with an attractive screen excited by a flat circular solenoid located on the outside of the auxiliary screen. Methodology. The calculations are shown that the induced currents both in the screen and the workpiece are unidirectional and their interaction, in accordance with the law of Ampere determines the amplitudes of excited forces of attraction. Let’s note the effective validity of the considered inductor system excited by an external circular solenoid. With sufficient simplicity of the design take place rather high valuesof the developed forces of attraction and their averages. Results. Physically, a higher power efficiency of the system with an «external» coil in comparison with a system where coil is located in the internal cavity, can be accounted for lade of «failure» in the radial distribution of the excited forces. This «failure» in the design with a coil between the sheet metal is causedby its screening action against the forces of attraction between the induced currents. Practical value. It is shown that the inductor system with an attractive screen when it is excited by outer circular solenoid with a current of 50 kA ~ provides attractive power rates to about 1400 N on an area of sheet metal ~ 0.004 m². The sufficiently high efficiency of the proposed options of an inductor system allows us to recommend it as a tool of the external straightening dents in the bodycar surfaces of vehicles.
Analysis of the processes in an inductor system with an attracting screen excited by the external circular solenoid
Keywords: обработка магнитно-импульсная; притяжение металлов; ток электрический; magnetic pulse treatment; attractive of metals